(untitled) (Journal of Medicine, 2024)
Hypereosinophilia is a rare collection of syndromes of various etiologies that can present incidentally or in some cases, in a life-threatening manner. This is a unique case of a 38-year-old male who presented with acute encephalopathy following a cerebrovascular event and was later found to have elevated eosinophil counts. It is crucial to have high clinical suspicion to diagnose this rare disease when a patient presents with multi-organ dysfunction with no clear etiology, especially when involving a presentation of acute onset in a relatively young patient. J MEDICINE 2024; 25: 94-97